KEBERADAAN GALERI INVESTASI BURSA EFEK INDONESIAUNIVERSITAS MUHAMMADIYAH GORONTALO TERHADAP MINAT MAHASISWA DALAM BERINVESTASI - Hiola, Yustina; Paris, Andika (JSAP : Journal Syariah and Accounting Public, 2020)
Indonesia Stock Exchange (IDX) Investment Gallery at Universitas Muhammadiyah Gorontalo is the first investment gallery in the University at Gorontalo Province. Since it was formed at the end of 2017, this investment gallery has had more than 100 stock investors. This research aimed to determine the existence of the stock exchange investment gallery at Universitas Muhammadiyah Gorontalo and its effect on the students’ investment interests. The researcher used the descriptive qualitative method. Data were collected by using a questionnaire that was distributed to 40 students of Universitas Muhammadiyah Gorontalo with two indicators, 1) understanding of galleries and 2) interest in investing. The results of the study showed that 45% or 18 respondents knew the existence of galleries, 42% or 17 respondents did not know the existence of galleries, and 13% or 5 respondents were doubtful. While the second indicator about investment interest, there were 46% or 19 respondents answered yes (interested), 33% or 13 who answered not interested, and 21% or 8 respondents were doubtful